PERAN KELUARGA DALAM MEMBENTUK PERKEMBANGAN SOSIAL ANAK DITINJAU DARI PERSPEKTIF ISLAM: A LITERATURE REVIEW - Nurasmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Children's social development is often solely associated with the quality of their peer relationships, whereas, in fact, the family plays the most crucial role in shaping children's social development. This scientific work aims to further explore the impact of the family in shaping children's social behavior based on Islamic principles. The research problem addressed is the importance of understanding children's social development within the family, as well as the need to explore the unique perspective of Islam in this context. The method used is a literature review. The study reviewed academic articles published between 2013 and 2022, obtained from Google Scholar. The article search process used the keywords “family,” “social development,” and “Islamic perspective.” The findings emphasize the diverse roles of the family in children's social development, which include functions such as education, protection, affection, socialization, reproduction, religious guidance, economic support, recreation, biological care, and cultural transmission. These roles are essential in nurturing the social and emotional well-being of children within the Islamic framework. The implications of this study are significant as they provide insights into the vital role of the family in children's social development from an Islamic perspective, making it a valuable reference for future research